Mechanism of aluminum carbide formation in aluminum electrolysis cells - Wang Y.-W.; Hao P.-C.; Peng J.-P.; Di Y.-Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The formation and dissolution of aluminum carbide is considered the primary factor affecting the life of aluminum electrolysis cells. Herein, the characteristics of sodium-graphite intercalation compounds (Na-GICs) were measured and the formation mechanism of Al4C3 during the aluminum electrolysis process was experimentally studied. The Na-GIC characteristics and the products of aluminum and Na-GIC reactions were investigated by Raman spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and scanning electron microscopy. The results showed that graphite can react with the sodium metal to form Na-GICs, which were detectable by Raman spectroscopy. Sodium inserted into the graphite layered structure acted as an intercalation agent to change the original graphite layered structure and increase the volume and specific surface area of graphite. Further, Al4C3 was produced by using sodium-graphite intercalation compounds and aluminum as materials. Thus, the presence of sodium plays an important role in the formation process of Al4C3 in aluminum electrolysis cells.